Evaluation of surface characteristics of new rotary nickel-titanium instruments: SEM-EDS analysis - Jovanović-Medojević Milica; Zdravković Alena; Medojević Mina; Stratimirović Đorđe (Serbian Medical Society - Dental Section, Belgrade, 2021)
Introduction Modern endodontic procedure implies the use of rotary Ni-Ti instruments during chemomechanical treatment of root canals. The aim of this study is to analyze the surfaces of new (unused) rotary endodontic instruments using the SEM-EDS method and determine how frequently manufacture defects or impurities appear on their working surfaces. Material and method Five new different sets of rotary endodontic Ni-Ti instruments were included in this study: K3, Mtwo, ProTaper Universal, HyFlex and BioRaCe. The working part of endodontic instrument was analyzed using SEMEDS method (magnifications ×150 to ×2000), which determined the morphological characteristics of the instrument surface and chemical composition of the found impurities. Statistical analysis was performed using the Fisher's test (p < 0.05). Results The results of SEM-EDS analysis showed that there is no new instrument without defects on its surface. The most common defects were observed in K3 (27.43%) and ProTaper Universal group (27.21%) and the least were in BioRaCe instruments (7.67%). The most common type of defect in tested instruments was fretting. In addition, the presence of debris and metal strips was found on all instruments, while corrosion of the working part was observed only in K3, ProTaper Universal and Mtwo systems in a small percentage. Conclusion Based on the results of this research, it can be concluded that manufacturing defects were noticed in all examined instruments. The most common defect is pitting. Impurities such as debris and metal strips have also been registered. No organic debris was observed on electropolished surface of BioRaCe instruments, but a small percentage of other types of defects were registered.